Vascular plant taxa occurrences in exotic woodland and in natural and production forests on the Islands of São Miguel, Terceira and Pico (Azores) - Lurdes Borges Silva; Patrícia Madeira; Diogo Pavão; Rui Elias; Monica Moura; Luís Silva (Biodiversity Data Journal, 2023)
The data presented here originated from field expeditions carried out between 2017 and 2018, within the framework of Forest-Eco2 project: "Towards an Ecological and Economic valorisation of the Azorean Forest". The project aimed to quantify the ecological value of the Azorean forests, including carbon accumulation and to design and propose measures that could further enhance forest sustainability. For that, 90 forest plots were sampled on three Azores islands - São Miguel, Terceira and Pico - equally distributed into natural forest, exotic woodland and production forest. The aim of this report is to further expand knowledge on biodiversity trends enclosed in the different forest types present in the Azores, by providing a list of the occurrences of the 105 different vascular plant taxa together with a brief characterisation of their origin and life-form.We provide an inventory of indigenous and non-indigenous vascular plant taxa from 90 forest stands. A total of 105 taxa were identified and registered, belonging to 60 families, 91 genera, 101 species and four subspecies. A total of 35% of the taxa were endemic, 27% native and 38% non-indigenous, including 19% of invasive taxa. Endangered and vulnerable taxa were registered, including Elaphoglossum hirtum (Sw.) C.Chr., Lactuca watsoniana Trel. and others which were considered by the authors a priority for conservation (e.g. Arceuthobium azoricum Wiens & Hawksw., Bellis azorica Hochst. ex Seub., Sanicula azorica Guthnick ex Seub., Platanthera micrantha (Hochst. ex Seub.) Schltr.). Our records provide detailed and updated knowledge of Azorean Forest flora and highlight the role of natural forests as indigenous plant diversity hotspots and exotic woodland as a source of invasive taxa within the Archipelago.